The Comparison of Conversational Structures between Zach Sang and The Radio 1 Breakfast Shows - Izza, Awwalia Fitrotin; Mujiyanto, Januarius; Yuliasri, Issy (Universitas Negeri Semarang, 2019)
This study focused on a comparison of conversational structures between two talk shows, Zach Sang Show and Radio 1 Breakfast Show. This study is a descriptive qualitative study. It used Zach Sang Show and Radio 1 Breakfast Show on an episode interview with Sam Smith as the object of the study. To analyze the data, the researcher used conversation analysis theory proposed by Schegloff and Sacks (1977). The result of the study revealed that both talk shows applied the structures of opening, closing, adjacency pairs, turn taking, and repairs. There are some similarities and differences between these two talk shows in terms of structures. High involvement style and high considerateness style appear in both shows. However, in Zach Sang Show, the two speakers mostly share the same style which is high considerateness style. In conclusion, there are some differences of conversational structures between Zach Sang Show and Radio 1 Breakfast Show on their interviews with Sam Smith. Keywords: Conversational Structures, Turn-Taking, Adjacency Pairs, Repairs, Conversation Style